A Glance at The History of Fergana Dance School - Hulkar Hamroeva (Zien Journals, 2021)
This article analyzes the creative activity and dances of the People's Artist of Uzbekistan, famous artist Mukarrama Turgunbaeva in the framework of the formation and development of the Fergana Dance School.
Keywords: Tanovar; values; terminology; Spring